Experimental manipulation of size and shape of tail spots and sexual selection in barn swallows - Møller, Anders P. (Curr Zool, 2017)
Barn swallows Hirundo rustica have white spots on their tail feathers, and they have been hypothesized to be a handicap because white spots are prone to feather breakage, ectoparasites are disproportionately common in white spots, and size of white spots increases with tail length. Here I test for attractiveness of narrow and long tail spots by manipulation of their shape while using complete painting of spots and an absence of treatment as a control. Female barn swallows are known to differentially invest in reproduction when mated to attractive males. Spot manipulation took place during laying of the first clutch, and there were no effects of treatment on clutch size or brood size of first or second broods. In contrast, the incidence of second clutches and the total number of eggs and fledglings produced during the breeding season was larger in males with painting of the side of tail spots rather than painting of the tip of spots, painting of entire spots, or no treatment. These findings are consistent with the hypothesis that it is the shape rather than the size of tail spots that affects differential reproductive effort by female barn swallows.